Pengolahan Sampah Organik Menggunakan Media Maggot Di Komunitas Bank Sampah Polaman Resik Sejahtera Kelurahan Polaman, Kecamatan Mijen, Kota Semarang - Anggun Puspitarini Siswanto; Mohamad Endy Yulianto; Hermawan Dwi Ariyanto; Nurul Pudiastutiningtyas; Elsan Febiyanti; Alvina Shafa Safira; Muhammad Iqbal Setya Wardana (Jurnal Pengabdian Vokasi, 2022)
[Bioconversion of Organic Waste using Balck Soldier Fly (BSF): In Collaboration with Resik Sejahtera Waste Community in Polaman Village, Semarang] In many developing countries, such as Indonesia, waste management remains a major issue. The community generates a large amount of waste, however the method for processing organic waste is still landfilling waste in the Final Processing Site (TPA). The amount of organic waste reached 65.05% in 2010, according to the Assessment and Application of Technology. As a result, organic waste processing solutions are required. The larva of the Black Soldier Fly, known as the maggot, is beneficial to humans and does not spread disease. Maggot is a type of animal feed that is regularly used. Maggots contain 43.42% protein, 17.24% fat, 18.82% crude fiber, 8.70% ash, and 10.79% water, making them a viable protein substitute. Furthermore, maggots are better at degrading organic waste than other insects. Maggot growing is the best way to deal with the community's organic waste problem. Community service activities have increased community members' and the Polaman Village community's knowledge and skills in organic waste processing using maggot media, which can reduce animal feed costs, vegetable compost costs, and increase community members' and the Polaman Village community's income.